Diretrizes para a elaboração de um novo manual do liquidante da SUSEP - Lima, Christian Alexandre Neves de (2015)
The intervention of the government in private entities is required in some circumstances. Regardless of the type of intervention, the actors involved are responsible for keeping the public interest and warrant that the intervention will not occur tighter than necessary. And the intervention must be performed pursuing quality and efficiency. The main issue is related to the intervention of the Government through the 'Superintendência de Seguros Privados' (Susep), authority that received from the Ministry of Financy the competency related to the control, regulation and supervision of important institutions: insurance/reinsurance companies, open private pension funds and capitalization entities. In this context, the monograph has focus on the extrajudicial liquidation, kind of intervention that occurs when there are signs of economic, financial, management crises or insolvency in the company. Susep delegates the procedures to the liquidator and supervises the process, whose focus must be the payments to creditors. It has been observed low efficiency in the management of the entities in liquidation, which in relevant part is due to the lack of guidelines for the preparation of the new Liquidator's Guide able to motivate efficient practices. Then the purpose herein is propose these guidelines. The research methodology is based on literature review, the collection and analysis of liquidators and experts’ opinion. The research will include the way some national or international authorities deal with the liquidation. We believe that the issue has great social relevance, because inefficiencies in such interventions can harm creditors, shareholders and generate waste of time and government ´s resources during the supervision of the liquidation. At the end of the monograph, we show the result: the proposed guidelines for the preparation of the new Liquidator's Guide.